Embodying Cape Town : Engaging the City through its Built Edges and Contact Zones - Jackson, Shannon M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book examines the reciprocity that exists between the body and the urban built environment. It will draw on archival and ethnographic research as well as an interdisciplinary literature on cultural materialism, semiotics, and aesthetics to challenge dualist interpretations of four different points of historical-material contact in Cape Town, South Africa. Each chapter attends to different groups, social practices, and historical periods, but all share the fundamental questions: how does material culture reflect the way social agents make meaning through bodily contact with urban built form, and how does such meaning challenge the ways bodies are objectified? Further, how can we make sense of the historical processes embedded in the objectification of bodies without treating the social and the material, the mental and the physical as separate realities? .
Keywords: Social sciences.; Ethnology -- Africa.; Urban geography.; Urban planning.; City planning.; Sociology, Urban.; elektronické knihy; electronic books